Investigation of homogeneous multi robots communication via bluetooth - Abdul Halim, Ismail (IEEE Conference Publications, 2014)
Proceedings of IEEE Symposium on Computer Applications and Industrial Electronics (ISCAIE 2012) at Kota Kinabalu, Malaysia on 3 December 2012 through 4 December 2012.